The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/nmat1784
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility window in zeolites

Abstract: Today synthetic zeolites are the most important catalysts in petrochemical refineries because of their high internal surface areas and molecular-sieving properties. There have been considerable efforts to synthesize new zeolites with specific pore geometries, to add to the 167 available at present. Millions of hypothetical structures have been generated on the basis of energy minimization, and there is an ongoing search for criteria capable of predicting new zeolite structures. Here we show, by geometric simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
239
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(250 citation statements)
references
References 24 publications
10
239
0
1
Order By: Relevance
“…Both analcime and pollucite thus lie towards the less dense edge of the flexibility window, consistent with the behaviour of other zeolite frameworks [11].…”
Section: Copyright C Epla 2011supporting
confidence: 82%
See 1 more Smart Citation
“…Both analcime and pollucite thus lie towards the less dense edge of the flexibility window, consistent with the behaviour of other zeolite frameworks [11].…”
Section: Copyright C Epla 2011supporting
confidence: 82%
“…It has recently been observed that known zeolite frameworks are typically perfectible over a wide range of densities [11]. This range is termed the "flexibility window".…”
Section: Copyright C Epla 2011mentioning
confidence: 99%
“…To explain this we take note of the beautiful work of Sartbaeva, Dawson and coworkers who showed that having some 'flexibility' is an important criterion in determining whether a zeolite can be successfully prepared. 16,17 Figure 5 shows how this concept can be applied to explain why the IPC-6 structure forms. The distance between these two layers is then fixed at that found for IPC-2P as the layers are connected by the rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the way the bodies are assembled, the structure can be rigid or flexible. If it is flexible, it can deform and the modes of 2 | Dalton Trans., 2015, 00, [1][2][3][4][5][6][7][8][9] This journal is © The Royal Society of Chemistry 2015 deformation are called mechanisms. A mechanism also corresponds to a degree of freedom of the structure.…”
Section: Flexibility Of Crystals and Organic Frameworkmentioning
confidence: 99%
“…A first class of approaches consists in exploring the phonon spectrum of zeolites and identifying vibration modes that conserve the shape and size of tetrahedra and have low frequency; these modes are variously referred to as rigid unit modes 14 (RUM) or floppy modes 15 depending on the implementation. More recently 9 , the concept of a flexibility window has emerged, where many zeolites remain flexible in a range of density; it is postulated that zeolites with a large flexibility window are more realisable 16,17 . In a few rare studies, rigid-units 18,19 and flexibility windows 20 type approaches have been applied to MOF-like structures.…”
Section: Flexibility Of Crystals and Organic Frameworkmentioning
confidence: 99%